Developing standards for surveying, measuring, and mapping underground objects using the GPR method for Vietnam - Nguyen, Phi Son; Nguyen, Thanh Thuy; Dao, Ngoc Long; Le, Chi Thinh; Nguyen, Thi Hue (Geodesy and Cartography, 2025)
In the context of rapid urbanization, detailed investigation of underground objects in the shallow layer is very important for safe and efficient urban planning, construction, and operation. With many outstanding advantages, Ground Penetrating Radar (GPR) technology has been increasingly applied worldwide in shallow geophysical surveys. However, in Vietnam, applying GPR for surveying and measuring objects in the above spatial range is only in its early stages, and there are no official standards or regulations. This paper uses the GPR method to develop technical standards for investigating and mapping underground objects within 0–6 m depth. The research methodology includes synthesis analysis of international standards, expert consultation, and field experiments. The main results of the study include: (1) Proposing a 9-step detailed GPR survey process; (2) Specific technical regulations for GPR survey work; (3) Classification of 4 quality levels of products (QLB1-QLB4) with specific requirements; (4) Guidelines for representing and presenting maps of underground objects. This standard will be the first document to standardize the application of GPR in measuring and acquiring information on underground objects in Vietnam, contributing to promoting the widespread application of GPR technology in practice.